Anonim ortaklıklarda temsil - Muynak, Burcu (My University, 2005)
TTK 317.md hükmünce anonim ortaklıklarda kanuni temsil organı Yönetim Kurulu'dur (YK). YK dışında kanunun belirttiği bazı durumlarda diğer organlar da temsil ile yetkili olabilir, TTK 319.md uyarınca da ortaklığı temsil ve yönetim yetkisi pay sahibi olan YK üyelerine veya pay sahibi olmayan üçüncü kişilere bırakılabilir.Ayrıca anonim ortaklığa ticari mümessil veya ticari vekil atanması da mümkündür.Anonim ortaklıkların ehliyetleri esas sözleşmelerinde yazılı işletme konuları ile sınırlıdır. Ehliyetin sınırları temsil yetkisinin sınırlarını da belirleyecektir. TTK 319.md gereğince yetkili temsilcilerin temsil yetkileri merkez ve şube işlerine hasredilmek suretiyle veya birlikte temsil kuralı ile sınırlandırılabilir.İşletme konusu dışında ortaklık tarafından yapılan işlemlerin ortaklık adına bağlı olmayacağı anlamına gelen ultra vires kuralı uygulamada büyük sorunlara neden olmaktadır. Bu nedenle ortaklığın hangi işlemlerle bağlı olup olmayacağı, üçüncü kişilerin menfaatlerini korunması, ortaklık konusu dışında yapılan işlemlerin hukuki sonuçları konusunda doktrinde tartışmalar mevcuttur. Bu bağlamda uygulamada yaşanan sorunlar, bu sorunlara getirilmek istenen çözümler ile artık uygulamasına bir çok ülkede son verilmiş olan ultra vires kuralı ile ilgili olarak diğer ülkelerde ve AT Hukukundaki gelişmeler ele alınmıştır. Name and Surname: Burcu MUYNAK Field: Law Programme: Private Law Supervisor: Prof.Dr. Merih Kemal OMAĞ Degree Awarded and Date: Master of Arts in Law, November 2005 Key Words: License, representation

REPRESANTATION IN İNCORPORATED COMPANIES According to the article 317 of Turkish Commercial Code (TCC), Executive Board (EB) is the body that is entitled to legally represent incorporated company . In certain cases described in TCC bodies other than EB can also legally represent corporations. As stipulated in the article 319 of TCC authority for representation and management of corporations can be given to members of executive board who are also share holders or to third party non share holders. Moreover, it is possible to appoint commercial agent or commercial representative to corporations. Scope of licence of incoporated firms are limited to magament issues declared in the articles association . The limit of license of incorpoarated firms will also delimit the representation authority accordingly. Article 319 of TCC stipulates that representation authority of authorized representatives can be confined to issues areas that are prerogatives of headquarter or branches or to principle of joint representation. Ultra vires principle-all operations and transactions that are out of company's field of activity do not bound the company in question-leads to serious problems in practice. Therefore, the issues such as which transactions bound corporations, protection of interests of third parties, juridical consequences of extra core business acts of corporations are controversial in doctrine. Within this framework, recent developments seen in other countries and European Community Law-concerning problems experienced in practice, proposed solutions to them, and ultra vires principle that is not in use in many countries- are taken up in this thesis.
Keywords: Özel Hukuk